Changes in Nutritional Status of 5-6 year old Children in Podgorica between 2013 and 2020 - Milica Vucerakovic; Milena Mitrovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2021)
The aim of this research was to analyze the level of nutrition of students enrolled in primary school in 2013 and students enrolled in primary school in 2020. The research includes data on the height and weight of children from the obligatory systematic examinations. These systematic examinations included a sample of 82 children. We divided them into four subsamples. The first subsample consists of 19 boys enrolled in school in 2013 (n = 19), and the second 18 girls enrolled in the same year (n = 18). The third subsample consists of 24 boys enrolled in 2020 (n = 24), and the fourth 21 girls enrolled in 2020 (n = 21). The measurement was performed by health workers at the PHI Health Center "Nova Varos" in Podgorica. Body mass and body height are determinated, and that was the basis for calculation of the body mass index (BMI). For all variables, were calculated the values of the measures of central and dispersion tendency. Differences in body parameters for assessing nutrition between children were determined using the t-test for small and independent samples and the Hi square test. The percentage of obese boys enrolled in 2013 was 28%, obese girls 0%, the percentage of obese boys enrolled in 2020 was 21%, and obese girls was 19%. There are statistically significant differences between boys measured in 2013 and 2020, in favor of boys measured in 2020. There are also statistically significant differences between girls measured in 2013 and 2020 (obese girls were measured in 2020). When it comes to comparing genders by age, there are statistically significant differences in favor of girls measured in 2013 and girls measured in 2020. It can be concluded that obesity is on the rise, given the fact that more obese children are enrolled in school in 2020.